Rupture in the 4 May 2018 MW 6.9 Earthquake Seaward of the Kilauea East Rift Zone Fissure Eruption in Hawaii. Issue 18 (19th September 2018) - Liu, Chengli; Lay, Thorne; Xiong, Xiong
Abstract: The 4 May 2018, M W 6.9 thrust‐faulting earthquake occurred a day after the first fissure eruption in Leilani Estates along the East Rift Zone of Kilauea, Hawaii, relatively early in the 2018 eruptive sequence. The earthquake's location and geodetic deformation pattern are similar to those of the larger 1975 Kalapana earthquake ( M W 7.7), which is thought to have occurred on the décollement between the island volcanics and the former Pacific seafloor. The 2018 event has a shallow‐dipping thrust plane and shallow epicenter located just offshore. A finite‐fault kinematic slip model is determined by inversion of teleseismic body waves, strong‐ground motion recordings, and coseismic Global Positioning System offsets along the southeastern coast of Hawaii. Inversions indicate a preferred dip of 7°, slip of up to 3.0 m near 5‐km deep offshore of the coast, and low average rupture speed of ~1 km/s. These are consistent with rupture of a weak décollement. Plain Language Summary: Early in the 2018 eruption sequence at Kilauea volcano in Hawaii, a magnitude 6.9 earthquake occurred just off the coast along the Leilani Estates which had begun to experience fissure eruptions a day earlier. The earthquake was well recorded by global seismic stations and by strong motion instruments on Hawaii, and Global Positioning System offsets during the earthquake were determined along the coastal area. These data are used to determine a space‐time history of the earthquake rupture. The slip is concentrated in a band offshore parallel to the coast, and the fault that ruptured is likely to be the boundary between the volcanic pile of the island and the former Pacific Ocean seafloor. As much as 3 m of slip occurred, with the rupture having behavior similar to slow rupturing tsunami earthquakes in subduction zones, indicating a relatively weak fault. Key Points: Teleseismic, strong‐motion, and GPS displacement data are inverted to determine the spatiotemporal earthquake slip distribution Peak slip is ~3.0 m, average rise time is 4.7 s, rupture speed is 0.7 to 1.6 km/s, and duration is 30 s, indicating low fault strength The earthquake likely ruptured the offshore shallow‐dipping décollement between the island volcanics and the former Pacific seafloor